GAMBARAN PENGETAHUAN KADER TENTANG DETEKSI RISIKO TINGGI IBU HAMIL DI WILAYAH KERJA PUSKESMAS BERANGAS - Lestari, Nur Cahyani Ari; Purwanti, Sri (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Local Area Monitoring Data for Maternal and Child Health (PWS-KIA) in Barito Kuala Regency, the coverage of detection of high-risk pregnant women by health workers is 47.3% of the 20% target, detection by cadres is 13.1% of the 80% target, and 2018 data regarding the coverage of detection of at-risk pregnant women by health workers at 47.2% of the 20% target and detection by cadres of 8.5% of the 80% target. This study was conducted with the aim of knowing the description of cadres' knowledge about detection of high risk of pregnant women in the work area of the Berangas Health Center. This study used a descriptive research method. The population and sample were all cadres who were in the work area of the Berangas Health Center. The data obtained using primary data and secondary data. The results of the study were 15 people (50%) had good knowledge, 12 people (40%) had sufficient knowledge and 3 people (10%) had poor knowledgeThe results of this study can be concluded that the level of knowledge of cadres about high risk detection of pregnant women in the work area of the Berangas Health Center is good.